SEMANTIC ANALYSIS OF WORDS BORROWED FROM THE ENGLISH LANGUAGE (Konferensiyalar | Conferences, 2024)
In this article, in a semantic analysis, we examine the consequences of the acquisition of English words and how their semantic structures may change when they are transferred to other languages. By studying the semantic adaptations, extensions, and shifts that occur during borrowing, we aim to unravel the complex interplay between language transfer, meaning construction, and cultural negotiation in the field of lexical borrowing. Through a deeper understanding of the semantic processing and integration of English-derived words into different linguistic frameworks, we can appreciate the dynamic nature of language communication and the richness of intercultural communication in a globalized world.